THE EFFECT OF USING INTERACTIVE LEARNING VIDEOS ON MOTIVATION AND PHYSICS LEARNING OUTCOMES - Hardianti Dian; Linda Sekar Utami; Johri Sabaryati (Jurnal Inovasi Fisika dan Edukasi, 2026)
The use of story-based instructional video represents a crucial aspect of physics education because students often encounter difficulties in understanding abstract concepts, leading to low conceptual comprehension and suboptimal learning outcomes. This issue necessitates further investigation into the effectiveness of integrating storytelling elements within video-based learning to enhance students’ conceptual understanding. This study aims to examine the effect of story-based learning videos on students’ conceptual understanding in physics. The research employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. Data were collected through conceptual understanding tests, supported by observation and documentation. The obtained data were analyzed using descriptive statistics and inferential analysis, including the t-test and N-gain calculation. The findings reveal that students taught using story-based instructional videos demonstrated a significant improvement in conceptual understanding, as evidenced by an increase in the mean score from 63.20 to 84.10 and an N-gain value of 0.72, categorized as high, along with a statistically significant difference between the experimental and control groups. These results indicate that the integration of storytelling in video-based learning effectively enhances students’ comprehension of abstract physics concepts and promotes more meaningful learning experiences. This study contributes significantly to the advancement of physics education at both national and international levels by providing an innovative, technology-enhanced pedagogical approach that supports interactive and engaging learning environments. Furthermore, the findings are expected to serve as a valuable reference for future research, particularly in the development of multimedia-based instructional strategies and the exploration of their long-term impact on conceptual understanding and higher-order thinking skills.